Gladys A. Varela y Ana María Biset. Neuquén: 10.000 años de historia. (Revista de Historia, 2014)
Gladys A. Varela y Ana María Biset. Neuquén: 10.000 años de historia. Neuquén. Calf- Aten. 1994 22 páginas